Value of Contrast-Enhanced Ultrasound in Mummified Thyroid Nodules - Chen, Sijie; Tang, Kui; Gong, Yi; Ye, Fei; Liao, Liyan; Li, Xiaodu; Zhang, Qi; Xu, Yan; Zhang, Rongsen; Niu, Chengcheng (Frontiers in Endocrinology, 2022)
Mummified thyroid nodules (MTNs) are rarely reported and are usually misdiagnosed as malignant nodules. This article first reviewed the contrast-enhanced ultrasound (CEUS) enhancement features of 218 MTNs and classified them into three (A, B, C) patterns. A pattern MTNs show linear hypo-enhancement, B pattern MTNs show heterogeneous hypo-enhancement and C pattern MTNs show no enhancement in thyroid nodules. The A and C pattern enhancement of MTNs demonstrated a high specificity compared with the enhancement of previously reported typical papillary thyroid carcinomas (PTCs). To further study the B pattern MTNs, 24 B pattern MTNs and 42 PTCs were enrolled in this study, and CEUS parameters for each nodule were evaluated. Univariate analysis indicated that compared with PTCs, the B pattern MTNs more frequently exhibited heterogeneous hypo-enhancement and clear margins after clearance (p < 0.05). A multivariate analysis revealed that heterogeneous hypo-enhancement and clear margins after clearance were independent characteristics related to B pattern MTNs for their differentiation from PTCs (p <0.05). Our study indicated that preoperative CEUS characteristics may serve as a useful tool for distinguishing MTNs from malignant thyroid nodules to avoid surgical excisions or unnecessary fine-needle aspiration (FNA).